Consensus of Chinese Experts on the Diagnosis and Treatment of Type Ⅰ Interferonopathy - Chinese Alliance of Pediatric Rheumatic & Immunologic Diseases; Chinese Pharmacists Association Rare Diseases Medication Working Committee (罕见病研究)
Type Ⅰ interferonopathy is an autoinflammatory disease that affects multiple systems, with a high disability and mortality rate. It profoundly impacts the quality of life of patients and poses a considerable burden on their families and society. Due to the broad spectrum of clinical phenotypes associated with this condition, early identification remains challenging. Delays in diagnosis and treatment can exacerbate the disease, making it difficult to reverse the conditions and adversely affecting the prognosis. Therefore, the Chinese Alliance of Pediatric Rheumatic & Immunologic Diseases and Chinese Pharmacists Association Rare Diseases Medication Working Committee has developed this consensus document to offer detailed recommendations pertaining to the definition, genetic categorization, clinical presentations, diagnostic approaches, and therapeutic management of type Ⅰ interferonopathy.